Отчего ива говорлива: [стихи / Герман Ходырев] - Ходырев Герман Алексеевич (Удмуртия, 1974)
Экземпляры: Аб (20220919) / Инвентарный номер: 118626 / Цена: 5.00 / Авт.знак: Х 69 / ГРНТИ: 17.82 / ББК: 84(2Рос=Удм)